Performance of sunflower (Helianthus annuus L.) hybrids under West Bengal condition: PERFORMANCE OF SUNFLOWER HYBRIDS UNDER WEST BENGAL CONDITION - A DUTTA (Journal of Oilseeds Research, 2015)
An experiment on the performance of various sunflower hybrids was carried out at Pulses and Oilseed Research Station (PORS), Berhampore during rabi (winter) 2013-14 under Initial Hybrid Trial (IHT) of AICRP (Sunflower) with 12 hybrids. Among the 12 hybrids, two hybrids WBSH-2021 and WBSH-2034 developed at PORS, Berhampore during winter 2012-13 were included in the trial. The experiment was laid out in Randomized Complete Block Design having four replications, with each sub plot size of 4.5 x 3.0 m2 . Statistical analysis of the data showed significant differences for all the parameters except days to 50% flowering, days to maturity and 100-seed weight. It was observed that WBSH-2021 registered 31%, 25% and 66% more seed yield and 30%, 29% and 70% more oil yield than the three check hybrids. Under zone-III, WBSH-2021 recorded 16%, 7% more seed yield and 11%, 15.3% more oil yield than the check hybrids DRSH-1 and KBSH-44, respectively. Based on the performance of the IHT the hybrid WBSH-2021 was promoted to Advanced Hybrid Trial (AHT) of AICRP (Sunflower).